Biological functions of LncRNA SNHG14 in the development of thyroid cancer cells via targeting miR-206: LncRNA SNHG14/miR-206 thyroid cancer - Sang, Yiming; Min, Rui; Huang, Tao; Zhang, Jizong (Cellular and Molecular Biology, 2024)
This study aimed to determine lncRNA SNHG14 and miR-206 in Thyroid Cancer ( TC) and to explore the related mechanisms. Sixty-four samples of thyroid tissue were collected from patients with TC. TC cell lines and a normal human thyroid cell line (HTori-3) were bought. lncRNA SNHG14-siRNA (si-lncRNA SNHG14), lncRNA SNHG14-shRNA (sh-lncRNA SNHG14), blank plasmid (siRNA-NC), miR-206-inhibitor, miR-206-mimics were transfected into BHT101 and Ocut-2C cells. qRT-PCR quantified the expression of lncRNA SNHG14 and miR-206, and the expression of vimentin, Snail, N-cadherin, Slug, E-cadherin and ZO-1 proteins were identified via WB. MTT assay, flow cytometry, and Transwell were employed to determine cellular proliferation, apoptosis, and invasion, separately. The high expression of lncRNA SNHG14 and low expression of miR-206 were exhibited in patients with TC. lncRNA SNHG14 and miR-206 were related to lymph node metastases, TNM staging, as well as differentiation of TC. Silencing lncRNA SNHG14 and over-expressing miR-206 inhibited cell EMT, proliferation, and invasion, but accelerated apoptosis. WB demonstrated that silencing lncRNA SNHG14 and over-expressing miR-206 suppressed the expression of Akt, p-ERK1/2, p-p38, p-4EBP1, p-Akt, PI3K, vimentin, Snail, N-cadherin, and Slugn, as well as up-regulated the expression of E-cadherin and ZO-1. Rescue experiment showed that after BHT101 and Ocut-2C cells were transfected with either sh-lncRNA SNHG14+miR-206-mimics or si-lncRNA SNHG14+miR-206-inhibitor, the cellular proliferative, invasive, and apoptotic activities weren't different from those transfected with siRNA-NC. Suppression of lncRNA SNHG14 up-regulates miR-206 and affects EMT, as well as proliferative, invasive, and apoptotic activities of cells, which may become an underlying treatment target for TC.